Strategi Komunikasi Komunitas Relawan Senabung Serang dalam Meningkatkan Eksistensi di Masyarakat Eksistensi di Masyarakat dan Pengaruhnya terhadap Partisipasi Sosial - Ades Sulfiah; Achmad Nashrudin Priatna; April Laksana; Noerma Kurnia Fajarwati; Meiby Zulfikar (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
The SENABUNG Serang Volunteer Community has various humanitarian programs to help the poor, street children, and other communities in need. This study aims to determine the communication strategy of the SENABUNG Serang Volunteer Community in increasing its presence in the community, as well as to analyze the obstacles faced. The research method uses a descriptive qualitative approach with the Resource Mobilization theory. Data were obtained through interviews, observation, and documentation. Data validity techniques use source triangulation to ensure the validity of the research findings. The results show that the existence of the SENABUNG community is built through the mobilization of five types of resources, namely human, material, organizational, socio-cultural, and moral resources. The community has succeeded in mobilizing volunteers, collecting donations, building social networks, and gaining moral legitimacy from the community. However, this study also found internal obstacles such as limited volunteers and time, inadequate equipment, unstable morale and transportation facilities, as well as external obstacles such as dependence on donations and digital security threats. Despite these successes, the study highlights significant challenges. Internally, the community struggles with a limited number of volunteers, which affects the sustainability of its programs. Moreover, the volunteers' time commitment is often restricted, limiting their capacity to engage fully. Additionally, inadequate equipment and unstable morale present further hurdles. Externally, the community's reliance on donations for funding leaves it vulnerable to fluctuations in contributions, and digital security threats pose risks to the integrity of the information shared across platforms.